High-temperature-resistant and corrosion-resistant polyvinyl chloride pipe and preparation method thereof
By adding specific additives to the polyvinyl chloride material, high-temperature and corrosion-resistant polyvinyl chloride material is formed, which solves the problem of thermal degradation and corrosion of polyvinyl chloride materials at high temperatures, and achieves significant thermal stability and corrosion resistance of the material. promote.
Patent Information
- Application Number
- CN202411268660.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-27
AI Technical Summary
Existing polyvinyl chloride materials are prone to thermal degradation and corrosion at high temperatures, which limits their application scope, and the prior art has failed to effectively improve their corrosion resistance.
By grafting chlorinated polyvinyl chloride, styrene-acrylonitrile copolymer, heat stabilizer and plasticizer in the polyvinyl chloride resin, combined with modified hydrotalcite and montmorillonite, it forms excellent heat resistance by grafting the chlorinated polyvinyl chloride, styrene-acrylonitrile copolymer, heat stabilizer and plasticizer in the polyvinyl chloride resin, and combining modified hydrotalcite and montmorillonite. Polyvinyl chloride material with corrosion resistance.
It significantly improves the thermal stability, mechanical properties and corrosion resistance of polyvinyl chloride materials, extends its service life at high temperatures, and enhances its stability to ultraviolet light.
Smart Images

Figure CN119192746A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a high-temperature resistant and corrosion-resistant polyvinyl chloride pipe and a preparation method thereof. Background Art
[0002] Polyvinyl chloride is a type of polymer material with excellent comprehensive properties. It has excellent mechanical properties, corrosion resistance, flame retardancy, etc., and is widely used in many fields. Polyvinyl chloride resin is formed by the polymerization of vinyl chloride under the action of an initiator. It is a non-crystalline, polar thermoplastic polymer. The polar bonds between its macromolecules make polyvinyl chloride hard and brittle. In addition, since polyvinyl chloride resin contains chlorine groups, when the temperature is too high, polyvinyl chloride will undergo a dehydrochlorination reaction, resulting in thermal degradation of the polyvinyl chloride resin. In actual production and application, since the processing temperature of polyvinyl chloride is higher than the decomposition temperature, it is easy to decompose during the processing, causing its mechanical properties to decrease. In addition, the use of pipes made of polyvinyl chloride as raw materials is limited at higher temperatures, which affects the application of polyvinyl chloride materials.
[0003] In the prior art, additives such as stabilizers and plasticizers are usually added during the processing of polyvinyl chloride to improve the comprehensive properties of polyvinyl chloride resin; the prior art, such as Chinese patent application CN101696306A, discloses a heat-resistant and wear-resistant PVC pipe, which improves the high temperature resistance and wear resistance of polyvinyl chloride resin by adding additives and chlorinated polyvinyl chloride resin to polyvinyl chloride resin. Although the polyvinyl chloride pipe prepared by the method has excellent high temperature resistance and wear resistance, it does not further improve other properties of the material such as corrosion resistance. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a high temperature resistant and corrosion resistant polyvinyl chloride pipe and a preparation method thereof. The polyvinyl chloride pipe is prepared from polyvinyl chloride material as raw material. The polyvinyl chloride material has excellent heat resistance and corrosion resistance, good mechanical properties, and can be used as a raw material to prepare polyvinyl chloride pipes.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0006] A method for preparing a high temperature resistant and corrosion resistant polyvinyl chloride material comprises the following steps:
[0007] Step (1), mixing maleimide monomer, styrene, methyl acrylate, modified hydrotalcite and dimethyl sulfoxide, adding azobisisobutyronitrile, reacting, filtering, washing and drying after the reaction is completed to obtain a thermal stabilizer;
[0008] Wherein, the maleimide monomer is prepared by the following steps:
[0009] N-(4-hydroxyphenyl)maleimide, paraformaldehyde and 1,4-dioxane are mixed and dissolved, p-methylaniline is added, and the reaction is carried out. After the reaction is completed, the solvent 1,4-dioxane is removed by rotary evaporation, a precipitant is added for precipitation, the mixture is allowed to stand, filtered and dried to obtain a maleimide monomer;
[0010] The modified hydrotalcite is prepared by the following steps:
[0011] The hydrotalcite is mixed with water by stirring, and a sodium dodecyl sulfate aqueous solution and acrylic acid are added as a regulator to adjust the pH value, and the reaction is carried out. After the reaction is completed, the mixture is cooled, filtered, washed, and dried to obtain a modified hydrotalcite;
[0012] Step (2), uniformly mixing polyvinyl chloride, maleic anhydride grafted chlorinated polyvinyl chloride, styrene-acrylonitrile copolymer, heat stabilizer and plasticizer, melt-extruding, cooling and pelletizing to obtain a high temperature resistant and corrosion resistant polyvinyl chloride material;
[0013] Wherein, the plasticizer is prepared by the following steps:
[0014] Mix benzophenone-4,4'-dicarboxylic acid, 1,10-decanediol and adipic acid, add stannous octoate, react, raise the temperature and continue the reaction, and obtain copolyester after the reaction is completed; mix the copolyester with montmorillonite, melt blend, extrude and granulate to obtain a plasticizer;
[0015] Maleic anhydride grafted chlorinated polyvinyl chloride comprises the following steps to prepare:
[0016] Chlorinated polyvinyl chloride is mixed with acetone to swell, and maleic anhydride aqueous solution and ammonium persulfate aqueous solution are added to react. After the reaction is completed, the mixture is filtered, washed, and dried to obtain maleic anhydride grafted chlorinated polyvinyl chloride.
[0017] Preferably, in the step (1), the mass ratio of maleimide monomer, styrene, methyl acrylate, modified hydrotalcite, dimethyl sulfoxide and azobisisobutyronitrile is 9-10:13-15:5-6:10:350-400:0.3-0.4; and the reaction conditions are: reacting at a temperature of 70-80°C for 20-24h.
[0018] Preferably, in the step (1) of preparing the maleimide monomer, the mass ratio of N-(4-hydroxyphenyl)maleimide, p-methylaniline, paraformaldehyde and 1,4-dioxane is 7.2-7.5:4.1-4.5:2.2-2.5:20-30; and the reaction conditions are: reacting at a temperature of 85-95° C. for 8-10 hours.
[0019] Preferably, the precipitating agent comprises diethyl ether.
[0020] Preferably, in the step (1) of preparing the modified hydrotalcite, the mass ratio of hydrotalcite, water, sodium dodecyl sulfate aqueous solution and acrylic acid aqueous solution is 1:25-30:28-30:25-28, the sodium dodecyl sulfate aqueous solution is 12wt% sodium dodecyl sulfate aqueous solution, and the acrylic acid aqueous solution is 3.5wt% acrylic acid aqueous solution; the reaction conditions are: reacting at a pH value of 4-5 and a temperature of 60-70°C for 3-4h.
[0021] Preferably, the regulator comprises 0.1 mol / L dilute nitric acid.
[0022] Preferably, in step (2), the mass ratio of polyvinyl chloride, maleic anhydride grafted chlorinated polyvinyl chloride, styrene-acrylonitrile copolymer, heat stabilizer and plasticizer is 100:20-25:4-6:8-10:5-6; and the melt extrusion conditions are: melt extrusion at a temperature of 170-180°C through a twin-screw extruder.
[0023] Preferably, in the step (2) of preparing the plasticizer, the molar ratio of benzophenone-4,4'-dicarboxylic acid, 1,10-decanediol and adipic acid is 0.8-1:5:4-4.2; the amount of stannous octoate added is 3% of the mass of 1,10-decanediol; the reaction conditions are: reacting for 5-6 hours at a temperature of 170-180°C in a nitrogen atmosphere; the continued reaction conditions are: continuing the reaction for 1.5-2 hours at a vacuum degree of 200-250Pa and a temperature of 200-220°C; the mass ratio of the copolyester to the montmorillonite is 100:20-30; and the melt blending conditions are: melt blending at a temperature of 110-120°C by a twin-screw extruder.
[0024] Preferably, in the step (2) of preparing maleic anhydride grafted chlorinated polyvinyl chloride: the mass ratio of chlorinated polyvinyl chloride, acetone, maleic anhydride aqueous solution, and ammonium persulfate aqueous solution is 20:180-220:50-55:45-50, the maleic anhydride aqueous solution is 4wt% maleic anhydride aqueous solution, and the ammonium persulfate aqueous solution is 1wt% ammonium persulfate aqueous solution; the reaction conditions are: reacting at a temperature of 80-90°C for 1.5-2h.
[0025] Preferably, a high temperature resistant and corrosion resistant polyvinyl chloride material is prepared by the method for preparing the high temperature resistant and corrosion resistant polyvinyl chloride material as described above.
[0026] Preferably, a high temperature resistant and corrosion resistant polyvinyl chloride pipe is prepared using the high temperature resistant and corrosion resistant polyvinyl chloride material as described above.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The invention adds maleic anhydride grafted chlorinated polyvinyl chloride, styrene-acrylonitrile copolymer, heat stabilizer and plasticizer into a polyvinyl chloride resin matrix, so that the prepared polyvinyl chloride material has excellent heat resistance and corrosion resistance, good mechanical properties, and can be used as a raw material to prepare polyvinyl chloride pipes.
[0029] Hydrotalcite is a type of anionic layered columnar compound composed of two metal hydroxides, which has an ion exchange function, can absorb hydrogen chloride released by thermal degradation of polyvinyl chloride, reduce the concentration of free hydrogen chloride in the matrix, effectively inhibit the self-catalytic degradation reaction of polyvinyl chloride by hydrogen chloride, and improve the thermal stability of polyvinyl chloride. The invention uses an ion exchange method to replace the original carbonate ions between the hydrotalcite layers with sodium dodecyl sulfate and acrylic acid, and introduces acrylic acid into the hydrotalcite interlayer while increasing the interlayer distance of the hydrotalcite. The prepared modified hydrotalcite can utilize the carbon-carbon double bonds of acrylic acid to react with other hydrotalcites having carbon-carbon double bonds. The monomers are reacted and copolymerized; the maleimide monomer obtained by mixing N-(4-hydroxyphenyl) maleimide with polyformaldehyde and p-methylaniline to undergo a Mannich reaction has a maleimide structure and an oxazine ring structure, both of which have good heat resistance. The maleimide monomer is used as a polymerization monomer, and the carbon-carbon double bond is used to react and copolymerize with modified hydrotalcite, styrene, and methyl acrylate to generate a block copolymer with good compatibility with polyvinyl chloride, thereby improving the compatibility of the modified hydrotalcite with the polyvinyl chloride matrix, and the obtained heat stabilizer can effectively improve the thermal stability of polyvinyl chloride;
[0030] The invention polymerizes benzophenone-4,4'-dicarboxylic acid with 1,10-decanediol and adipic acid to obtain a copolyester with ultraviolet absorption function, melts and blends the copolyester with montmorillonite, and in-situ intercalates the copolyester with montmorillonite. The obtained plasticizer can not only plasticize polyvinyl chloride, but also be used as a light stabilizer to improve the light stability of polyvinyl chloride; polyvinyl chloride, maleic anhydride grafted chlorinated polyvinyl chloride, styrene-acrylonitrile copolymer, heat stabilizer and plasticizer are melt-extruded to obtain a high temperature resistant and corrosion resistant polyvinyl chloride material;
[0031] Among them, maleic anhydride grafted chlorosulfonated polyvinyl chloride can improve the heat resistance and mechanical properties of the polyvinyl chloride matrix; the acrylonitrile structure in the styrene-acrylonitrile copolymer has a good interaction force with polar groups such as the chlorine atoms of polyvinyl chloride, which can promote the plasticization of polyvinyl chloride during processing and melting, and because the styrene-acrylonitrile copolymer and the substituted acrylonitrile ultraviolet absorber have a partially similar structure and a strong absorption capacity for ultraviolet light, they can inhibit the rate of dehydrochlorination of polyvinyl chloride and synergize with the plasticizer to improve the photostability of polyvinyl chloride; the hydrotalcite in the heat stabilizer and the montmorillonite in the plasticizer both have a layered structure, which can extend the path of corrosion penetration when dispersed in the polyvinyl chloride matrix, further improving the corrosion resistance of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a process flow chart for preparing a high temperature resistant and corrosion resistant polyvinyl chloride pipe in the present invention;
[0033] Figure 2 It is a Vicat softening temperature bar chart of the comprehensive performance test of the high temperature resistant and corrosion resistant polyvinyl chloride materials prepared in Examples 1-5 and Comparative Examples 1-3 of the present invention;
[0034] Figure 3 It is a bar chart of the corrosion resistance performance in the comprehensive performance test of the high temperature resistant and corrosion resistant polyvinyl chloride materials prepared in Examples 1-5 and Comparative Examples 1-3 of the present invention. DETAILED DESCRIPTION
[0035] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0036] Example 1
[0037] This embodiment discloses a method for preparing a high temperature resistant and corrosion resistant polyvinyl chloride material, comprising the following steps:
[0038] Step (1), mixing maleimide monomer, styrene, methyl acrylate, modified hydrotalcite, and dimethyl sulfoxide, adding azobisisobutyronitrile, the mass ratio of maleimide monomer, styrene, methyl acrylate, modified hydrotalcite, dimethyl sulfoxide, and azobisisobutyronitrile is 9:13:5:10:350:0.3, reacting at 70°C for 24h, after the reaction is completed, filtering, taking the filter cake, adding 5 times the mass of the filter cake for washing, and drying at 50°C for 16h to obtain a thermal stabilizer;
[0039] Wherein, the maleimide monomer is prepared by the following steps:
[0040] Mix and dissolve N-(4-hydroxyphenyl)maleimide, paraformaldehyde, and 1,4-dioxane, add p-methylaniline, the mass ratio of N-(4-hydroxyphenyl)maleimide, p-methylaniline, paraformaldehyde, and 1,4-dioxane is 7.2:4.1:2.2:20, react at 85°C for 10 hours, and after the reaction, remove the solvent 1,4-dioxane by rotary evaporation at 80°C to obtain a reaction product, add ether 5 times the mass of the reaction product to precipitate, let stand for 0.5 hours, filter, take the filter cake, and dry it at 50°C for 16 hours to obtain a maleimide monomer;
[0041] Wherein, the modified hydrotalcite is prepared by the following steps:
[0042] The hydrotalcite and water were stirred and mixed at a temperature of 40° C., 12 wt % sodium dodecyl sulfate aqueous solution and 3.5 wt % acrylic acid aqueous solution were added, the mass ratio of hydrotalcite, water, 12 wt % sodium dodecyl sulfate aqueous solution and 3.5 wt % acrylic acid aqueous solution was 1:25:28:25, 0.1 mol / L dilute nitric acid was added to adjust the pH value to 4, the reaction was carried out at a temperature of 60° C. for 4 h, and after the reaction was completed, the mixture was cooled to room temperature, filtered, and the filter cake was taken, and water 5 times the mass of the filter cake was added to wash until it was neutral, and dried at a temperature of 50° C. for 20 h to obtain a modified hydrotalcite;
[0043] Step (2), polyvinyl chloride, maleic anhydride grafted chlorinated polyvinyl chloride, styrene-acrylonitrile copolymer, heat stabilizer and plasticizer are uniformly mixed in a mass ratio of 100:20:4:8:5, melt-extruded at a temperature of 170° C. through a twin-screw extruder, cooled and pelletized to obtain a high temperature resistant and corrosion resistant polyvinyl chloride material;
[0044] Wherein, the plasticizer is prepared by the following steps:
[0045] Benzophenone-4,4'-dicarboxylic acid, 1,10-decanediol and adipic acid are mixed in a molar ratio of 0.8:5:4.2, stannous octoate is added, and the amount of stannous octoate added is 3% of the mass of 1,10-decanediol, and the mixture is reacted for 6 hours at 170°C in a nitrogen atmosphere. After the reaction is completed, the temperature is increased, and the reaction is continued for 2 hours at a vacuum degree of 200Pa and a temperature of 200°C. After the reaction is completed, a copolyester is obtained; the copolyester is mixed with montmorillonite in a mass ratio of 100:20, melt-blended at 110°C by a twin-screw extruder, and extruded into granules to obtain a plasticizer;
[0046] Wherein, maleic anhydride grafted chlorinated polyvinyl chloride comprises the following steps to prepare:
[0047] Chlorinated polyvinyl chloride and acetone were mixed and swelled at 80°C for 1 hour, and 4wt% maleic anhydride aqueous solution and 1wt% ammonium persulfate aqueous solution were added, the mass ratio of chlorinated polyvinyl chloride, acetone, 4wt% maleic anhydride aqueous solution and 1wt% ammonium persulfate aqueous solution was 20:180:50:45, and the mixture was reacted at 80°C for 2 hours. After the reaction was completed, the filter cake was filtered and washed with 70°C hot water 5 times the mass of the filter cake, and dried at 70°C for 8 hours to obtain maleic anhydride grafted chlorinated polyvinyl chloride.
[0048] Example 2
[0049] This embodiment discloses a method for preparing a high temperature resistant and corrosion resistant polyvinyl chloride material, comprising the following steps:
[0050] Step (1), mixing maleimide monomer, styrene, methyl acrylate, modified hydrotalcite, and dimethyl sulfoxide, adding azobisisobutyronitrile, the mass ratio of maleimide monomer, styrene, methyl acrylate, modified hydrotalcite, dimethyl sulfoxide, and azobisisobutyronitrile is 9.3:13.5:5.3:10:360:0.33, reacting at 75°C for 22h, filtering after the reaction, taking the filter cake, adding water 6 times the mass of the filter cake for washing, and drying at 55°C for 14h to obtain a thermal stabilizer;
[0051] Wherein, the maleimide monomer is prepared by the following steps:
[0052] N-(4-hydroxyphenyl)maleimide, paraformaldehyde and 1,4-dioxane were mixed and dissolved, p-methylaniline was added, the mass ratio of N-(4-hydroxyphenyl)maleimide, p-methylaniline, paraformaldehyde and 1,4-dioxane was 7.3:4.2:2.3:23, and the mixture was reacted at 90°C for 9 hours. After the reaction was completed, the solvent 1,4-dioxane was removed by rotary evaporation at 80°C to obtain a reaction product, ether 5 times the mass of the reaction product was added for precipitation, the mixture was allowed to stand for 0.5 hours, filtered, the filter cake was taken, and dried at 55°C for 14 hours to obtain a maleimide monomer;
[0053] Wherein, the modified hydrotalcite is prepared by the following steps:
[0054] The hydrotalcite and water were stirred and mixed at a temperature of 40° C., 12 wt % sodium dodecyl sulfate aqueous solution and 3.5 wt % acrylic acid aqueous solution were added, the mass ratio of hydrotalcite, water, 12 wt % sodium dodecyl sulfate aqueous solution and 3.5 wt % acrylic acid aqueous solution was 1:26:28.5:26, 0.1 mol / L dilute nitric acid was added to adjust the pH value to 4, the reaction was carried out at a temperature of 65° C. for 3 h, and after the reaction was completed, the mixture was cooled to room temperature, filtered, and the filter cake was taken, and water 6 times the mass of the filter cake was added to wash until it was neutral, and dried at a temperature of 55° C. for 18 h to obtain a modified hydrotalcite;
[0055] Step (2), polyvinyl chloride, maleic anhydride grafted chlorinated polyvinyl chloride, styrene-acrylonitrile copolymer, heat stabilizer and plasticizer are uniformly mixed in a mass ratio of 100:21:4.5:8.5:5.3, melt-extruded at a temperature of 170° C. through a twin-screw extruder, cooled and pelletized to obtain a high temperature resistant and corrosion resistant polyvinyl chloride material;
[0056] Wherein, the plasticizer is prepared by the following steps:
[0057] Benzophenone-4,4'-dicarboxylic acid, 1,10-decanediol and adipic acid are mixed in a molar ratio of 0.85:5:4.15, stannous octoate is added, and the amount of stannous octoate added is 3% of the mass of 1,10-decanediol, and the mixture is reacted at 175°C for 5 hours in a nitrogen atmosphere. After the reaction is completed, the mixture is heated and the mixture is continued to react for 1.5 hours at a vacuum degree of 230Pa and a temperature of 210°C. After the reaction is completed, a copolyester is obtained; the copolyester is mixed with montmorillonite in a mass ratio of 100:22, melt-blended at 110°C by a twin-screw extruder, and extruded into granules to obtain a plasticizer;
[0058] Wherein, maleic anhydride grafted chlorinated polyvinyl chloride comprises the following steps to prepare:
[0059] Chlorinated polyvinyl chloride and acetone were mixed and swelled at 80°C for 1 hour, and 4wt% maleic anhydride aqueous solution and 1wt% ammonium persulfate aqueous solution were added, the mass ratio of chlorinated polyvinyl chloride, acetone, 4wt% maleic anhydride aqueous solution and 1wt% ammonium persulfate aqueous solution was 20:190:52:46, and the mixture was reacted at 85°C for 2 hours. After the reaction was completed, the filter cake was filtered and washed with 75°C hot water 5 times the mass of the filter cake, and dried at 75°C for 7 hours to obtain maleic anhydride grafted chlorinated polyvinyl chloride.
[0060] Example 3
[0061] This embodiment discloses a method for preparing a high temperature resistant and corrosion resistant polyvinyl chloride material, comprising the following steps:
[0062] Step (1), mixing maleimide monomer, styrene, methyl acrylate, modified hydrotalcite, and dimethyl sulfoxide, adding azobisisobutyronitrile, the mass ratio of maleimide monomer, styrene, methyl acrylate, modified hydrotalcite, dimethyl sulfoxide, and azobisisobutyronitrile is 9.5:14:5.5:10:370:0.35, reacting at 75°C for 22h, filtering after the reaction, taking the filter cake, adding water 6 times the mass of the filter cake for washing, and drying at 55°C for 14h to obtain a thermal stabilizer;
[0063] Wherein, the maleimide monomer is prepared by the following steps:
[0064] N-(4-hydroxyphenyl)maleimide, paraformaldehyde and 1,4-dioxane were mixed and dissolved, p-methylaniline was added, the mass ratio of N-(4-hydroxyphenyl)maleimide, p-methylaniline, paraformaldehyde and 1,4-dioxane was 7.35:4.3:2.35:25, and the mixture was reacted at 90°C for 9 hours. After the reaction was completed, the solvent 1,4-dioxane was removed by rotary evaporation at 80°C to obtain a reaction product, ether 5 times the mass of the reaction product was added for precipitation, the mixture was allowed to stand for 0.8 hours, filtered, the filter cake was taken, and dried at 55°C for 14 hours to obtain a maleimide monomer;
[0065] Wherein, the modified hydrotalcite is prepared by the following steps:
[0066] The hydrotalcite and water were stirred and mixed at a temperature of 45° C., 12 wt % sodium dodecyl sulfate aqueous solution and 3.5 wt % acrylic acid aqueous solution were added, the mass ratio of hydrotalcite, water, 12 wt % sodium dodecyl sulfate aqueous solution and 3.5 wt % acrylic acid aqueous solution was 1:28:29:26.5, 0.1 mol / L dilute nitric acid was added to adjust the pH value to 4.5, the reaction was carried out at a temperature of 65° C. for 3.5 h, and after the reaction was completed, the mixture was cooled to room temperature, filtered, and the filter cake was taken, and water 6 times the mass of the filter cake was added to wash until it was neutral, and dried at a temperature of 55° C. for 18 h to obtain a modified hydrotalcite;
[0067] Step (2), polyvinyl chloride, maleic anhydride grafted chlorinated polyvinyl chloride, styrene-acrylonitrile copolymer, heat stabilizer and plasticizer are uniformly mixed in a mass ratio of 100:23:5:9:5.5, melt-extruded at a temperature of 175° C. through a twin-screw extruder, cooled and pelletized to obtain a high temperature resistant and corrosion resistant polyvinyl chloride material;
[0068] Wherein, the plasticizer is prepared by the following steps:
[0069] Benzophenone-4,4'-dicarboxylic acid, 1,10-decanediol and adipic acid are mixed in a molar ratio of 0.9:5:4.1, stannous octoate is added, and the amount of stannous octoate added is 3% of the mass of 1,10-decanediol, and the reaction is carried out in a nitrogen atmosphere at a temperature of 175°C for 5.5 hours. After the reaction is completed, the temperature is increased, and the reaction is continued for 1.8 hours at a vacuum degree of 230Pa and a temperature of 210°C. After the reaction is completed, a copolyester is obtained; the copolyester is mixed with montmorillonite in a mass ratio of 100:25, melt-blended at a temperature of 115°C by a twin-screw extruder, and extruded into granules to obtain a plasticizer;
[0070] Wherein, maleic anhydride grafted chlorinated polyvinyl chloride comprises the following steps to prepare:
[0071] Chlorinated polyvinyl chloride and acetone were mixed and swelled at 80°C for 0.8h, and 4wt% maleic anhydride aqueous solution and 1wt% ammonium persulfate aqueous solution were added, the mass ratio of chlorinated polyvinyl chloride, acetone, 4wt% maleic anhydride aqueous solution and 1wt% ammonium persulfate aqueous solution was 20:200:53:48, and the mixture was reacted at 85°C for 1.8h. After the reaction was completed, the filter cake was filtered and washed with 75°C hot water 6 times the mass of the filter cake, and dried at 75°C for 7h to obtain maleic anhydride grafted chlorinated polyvinyl chloride.
[0072] Example 4
[0073] This embodiment discloses a method for preparing a high temperature resistant and corrosion resistant polyvinyl chloride material, comprising the following steps:
[0074] Step (1), mixing maleimide monomer, styrene, methyl acrylate, modified hydrotalcite, and dimethyl sulfoxide, adding azobisisobutyronitrile, the mass ratio of maleimide monomer, styrene, methyl acrylate, modified hydrotalcite, dimethyl sulfoxide, and azobisisobutyronitrile is 9.8:14.5:5.8:10:380:0.35, reacting at 75°C for 22h, after the reaction is completed, filtering, taking the filter cake, adding water 6 times the mass of the filter cake for washing, and drying at 55°C for 14h to obtain a thermal stabilizer;
[0075] Wherein, the maleimide monomer is prepared by the following steps:
[0076] N-(4-hydroxyphenyl)maleimide, paraformaldehyde and 1,4-dioxane were mixed and dissolved, p-methylaniline was added, the mass ratio of N-(4-hydroxyphenyl)maleimide, p-methylaniline, paraformaldehyde and 1,4-dioxane was 7.4:4.4:2.4:28, and the mixture was reacted at 95°C for 9 hours. After the reaction was completed, the solvent 1,4-dioxane was removed by rotary evaporation at 80°C to obtain a reaction product, ether 5 times the mass of the reaction product was added for precipitation, the mixture was allowed to stand for 1 hour, filtered, the filter cake was taken, and dried at 55°C for 14 hours to obtain a maleimide monomer;
[0077] Wherein, the modified hydrotalcite is prepared by the following steps:
[0078] The hydrotalcite and water were stirred and mixed at a temperature of 45°C, and a 12wt% aqueous solution of sodium dodecyl sulfate and a 3.5wt% aqueous solution of acrylic acid were added, wherein the mass ratio of the hydrotalcite, water, the 12wt% aqueous solution of sodium dodecyl sulfate and the 3.5wt% aqueous solution of acrylic acid was 1:29:29.5:27, and 0.1mol / L dilute nitric acid was added to adjust the pH value to 5, and the mixture was reacted at a temperature of 70°C for 3.5h. After the reaction was completed, the mixture was cooled to room temperature, filtered, and the filter cake was taken, and water 6 times the mass of the filter cake was added to wash the mixture until it was neutral, and the mixture was dried at a temperature of 55°C for 18h to obtain a modified hydrotalcite;
[0079] Step (2), polyvinyl chloride, maleic anhydride grafted chlorinated polyvinyl chloride, styrene-acrylonitrile copolymer, heat stabilizer and plasticizer are uniformly mixed in a mass ratio of 100:24:5.5:9.5:5.8, melt-extruded at a temperature of 180° C. through a twin-screw extruder, cooled and pelletized to obtain a high temperature resistant and corrosion resistant polyvinyl chloride material;
[0080] Wherein, the plasticizer is prepared by the following steps:
[0081] Benzophenone-4,4'-dicarboxylic acid, 1,10-decanediol and adipic acid are mixed in a molar ratio of 0.95:5:4.05, stannous octoate is added, and the amount of stannous octoate added is 3% of the mass of 1,10-decanediol, and the reaction is carried out in a nitrogen atmosphere at a temperature of 180°C for 5.5 hours. After the reaction is completed, the temperature is increased, and the reaction is continued for 1.8 hours at a vacuum degree of 250Pa and a temperature of 220°C. After the reaction is completed, a copolyester is obtained; the copolyester is mixed with montmorillonite in a mass ratio of 100:28, melt-blended at a temperature of 120°C by a twin-screw extruder, and extruded into granules to obtain a plasticizer;
[0082] Wherein, maleic anhydride grafted chlorinated polyvinyl chloride comprises the following steps to prepare:
[0083] Chlorinated polyvinyl chloride was mixed with acetone at 85°C and swelled for 0.5h. A 4wt% aqueous maleic anhydride solution and a 1wt% aqueous ammonium persulfate solution were added. The mass ratio of chlorinated polyvinyl chloride, acetone, 4wt% aqueous maleic anhydride solution and 1wt% aqueous ammonium persulfate solution was 20:210:54:49. The mixture was reacted at 85°C for 2h. After the reaction was completed, the filter cake was filtered and washed with 80°C hot water 6 times the mass of the filter cake. The mixture was dried at 75°C for 7h to obtain maleic anhydride grafted chlorinated polyvinyl chloride.
[0084] Example 5
[0085] This embodiment discloses a method for preparing a high temperature resistant and corrosion resistant polyvinyl chloride material, comprising the following steps:
[0086] Step (1), mixing maleimide monomer, styrene, methyl acrylate, modified hydrotalcite, and dimethyl sulfoxide, adding azobisisobutyronitrile, the mass ratio of maleimide monomer, styrene, methyl acrylate, modified hydrotalcite, dimethyl sulfoxide, and azobisisobutyronitrile is 10:15:6:10:400:0.4, reacting at 80°C for 20h, filtering after the reaction, taking the filter cake, adding 8 times the mass of the filter cake for washing, and drying at 60°C for 12h to obtain a thermal stabilizer;
[0087] Wherein, the maleimide monomer is prepared by the following steps:
[0088] Mix and dissolve N-(4-hydroxyphenyl)maleimide, paraformaldehyde, and 1,4-dioxane, add p-methylaniline, the mass ratio of N-(4-hydroxyphenyl)maleimide, p-methylaniline, paraformaldehyde, and 1,4-dioxane is 7.5:4.5:2.5:30, react at 95°C for 8h, and after the reaction, remove the solvent 1,4-dioxane by rotary evaporation at 80°C to obtain a reaction product, add ether 6 times the mass of the reaction product to precipitate, let stand for 1h, filter, take the filter cake, and dry it at 60°C for 12h to obtain a maleimide monomer;
[0089] Wherein, the modified hydrotalcite is prepared by the following steps:
[0090] The hydrotalcite and water were stirred and mixed at a temperature of 50° C., 12 wt % sodium dodecyl sulfate aqueous solution and 3.5 wt % acrylic acid aqueous solution were added, the mass ratio of hydrotalcite, water, 12 wt % sodium dodecyl sulfate aqueous solution and 3.5 wt % acrylic acid aqueous solution was 1:30:30:28, 0.1 mol / L dilute nitric acid was added to adjust the pH value to 5, the reaction was carried out at a temperature of 70° C. for 3 h, and after the reaction was completed, the mixture was cooled to room temperature, filtered, and the filter cake was taken, and water 8 times the mass of the filter cake was added to wash until it was neutral, and dried at a temperature of 60° C. for 16 h to obtain a modified hydrotalcite;
[0091] Step (2), polyvinyl chloride, maleic anhydride grafted chlorinated polyvinyl chloride, styrene-acrylonitrile copolymer, heat stabilizer and plasticizer are uniformly mixed in a mass ratio of 100:25:6:10:6, melt-extruded at a temperature of 180° C. through a twin-screw extruder, cooled and pelletized to obtain a high temperature resistant and corrosion resistant polyvinyl chloride material;
[0092] Wherein, the plasticizer is prepared by the following steps:
[0093] Benzophenone-4,4'-dicarboxylic acid, 1,10-decanediol and adipic acid are mixed in a molar ratio of 1:5:4, stannous octoate is added, and the amount of stannous octoate added is 3% of the mass of 1,10-decanediol, and the mixture is reacted at 180°C for 5 hours in a nitrogen atmosphere. After the reaction is completed, the mixture is heated and the mixture is continued to react for 1.5 hours at a vacuum degree of 250Pa and a temperature of 220°C. After the reaction is completed, a copolyester is obtained; the copolyester is mixed with montmorillonite in a mass ratio of 100:30, melt-blended at 120°C by a twin-screw extruder, and extruded into granules to obtain a plasticizer;
[0094] Wherein, maleic anhydride grafted chlorinated polyvinyl chloride comprises the following steps to prepare:
[0095] Chlorinated polyvinyl chloride and acetone were mixed and swelled at 85°C for 0.5h, 4wt% maleic anhydride aqueous solution and 1wt% ammonium persulfate aqueous solution were added, the mass ratio of chlorinated polyvinyl chloride, acetone, 4wt% maleic anhydride aqueous solution and 1wt% ammonium persulfate aqueous solution was 20:220:55:50, and the mixture was reacted at 90°C for 1.5h. After the reaction was completed, the filter cake was taken and washed with 80°C hot water 8 times the mass of the filter cake, and dried at 80°C for 6h to obtain maleic anhydride grafted chlorinated polyvinyl chloride.
[0096] Comparative Example 1
[0097] This comparative example discloses a method for preparing a polyvinyl chloride material, comprising the following steps:
[0098] Polyvinyl chloride, maleic anhydride grafted chlorinated polyvinyl chloride, styrene-acrylonitrile copolymer, hydrotalcite and plasticizer are uniformly mixed in a mass ratio of 100:20:4:8:5, melt-extruded at a temperature of 170° C. through a twin-screw extruder, cooled and pelletized to obtain a polyvinyl chloride material;
[0099] Wherein, the plasticizer is prepared by the following steps:
[0100] Benzophenone-4,4'-dicarboxylic acid, 1,10-decanediol and adipic acid are mixed in a molar ratio of 0.8:5:4.2, stannous octoate is added, and the amount of stannous octoate added is 3% of the mass of 1,10-decanediol, and the mixture is reacted for 6 hours at 170°C in a nitrogen atmosphere. After the reaction is completed, the temperature is increased, and the reaction is continued for 2 hours at a vacuum degree of 200Pa and a temperature of 200°C. After the reaction is completed, a copolyester is obtained; the copolyester is mixed with montmorillonite in a mass ratio of 100:20, melt-blended at 110°C by a twin-screw extruder, and extruded into granules to obtain a plasticizer;
[0101] Wherein, maleic anhydride grafted chlorinated polyvinyl chloride comprises the following steps to prepare:
[0102] Chlorinated polyvinyl chloride and acetone were mixed and swelled at 80°C for 1 hour, and 4wt% maleic anhydride aqueous solution and 1wt% ammonium persulfate aqueous solution were added, the mass ratio of chlorinated polyvinyl chloride, acetone, 4wt% maleic anhydride aqueous solution and 1wt% ammonium persulfate aqueous solution was 20:180:50:45, and the mixture was reacted at 80°C for 2 hours. After the reaction was completed, the filter cake was filtered and washed with 70°C hot water 5 times the mass of the filter cake, and dried at 70°C for 8 hours to obtain maleic anhydride grafted chlorinated polyvinyl chloride.
[0103] Comparative Example 2
[0104] This comparative example discloses a method for preparing a polyvinyl chloride material, comprising the following steps:
[0105] Step (1), mixing styrene, methyl acrylate, modified hydrotalcite and dimethyl sulfoxide, adding azobisisobutyronitrile, the mass ratio of styrene, methyl acrylate, modified hydrotalcite, dimethyl sulfoxide and azobisisobutyronitrile is 13:5:10:350:0.3, reacting at 70°C for 24h, filtering after the reaction, taking the filter cake, adding water 5 times the mass of the filter cake for washing, and drying at 50°C for 16h to obtain a thermal stabilizer;
[0106] Wherein, the modified hydrotalcite is prepared by the following steps:
[0107] The hydrotalcite and water were stirred and mixed at a temperature of 40° C., 12 wt % sodium dodecyl sulfate aqueous solution and 3.5 wt % acrylic acid aqueous solution were added, the mass ratio of hydrotalcite, water, 12 wt % sodium dodecyl sulfate aqueous solution and 3.5 wt % acrylic acid aqueous solution was 1:25:28:25, 0.1 mol / L dilute nitric acid was added to adjust the pH value to 4, the reaction was carried out at a temperature of 60° C. for 4 h, and after the reaction was completed, the mixture was cooled to room temperature, filtered, and the filter cake was taken, and water 5 times the mass of the filter cake was added to wash until it was neutral, and dried at a temperature of 50° C. for 20 h to obtain a modified hydrotalcite;
[0108] Step (2), polyvinyl chloride, maleic anhydride grafted chlorinated polyvinyl chloride, styrene-acrylonitrile copolymer, heat stabilizer and plasticizer are uniformly mixed in a mass ratio of 100:20:4:8:5, melt-extruded at a temperature of 170° C. through a twin-screw extruder, cooled and pelletized to obtain a polyvinyl chloride material;
[0109] Wherein, the plasticizer is prepared by the following steps:
[0110] Benzophenone-4,4'-dicarboxylic acid, 1,10-decanediol and adipic acid are mixed in a molar ratio of 0.8:5:4.2, stannous octoate is added, and the amount of stannous octoate added is 3% of the mass of 1,10-decanediol, and the mixture is reacted for 6 hours at 170°C in a nitrogen atmosphere. After the reaction is completed, the temperature is increased, and the reaction is continued for 2 hours at a vacuum degree of 200Pa and a temperature of 200°C. After the reaction is completed, a copolyester is obtained; the copolyester is mixed with montmorillonite in a mass ratio of 100:20, melt-blended at 110°C by a twin-screw extruder, and extruded into granules to obtain a plasticizer;
[0111] Wherein, maleic anhydride grafted chlorinated polyvinyl chloride comprises the following steps to prepare:
[0112] Chlorinated polyvinyl chloride and acetone were mixed and swelled at 80°C for 1 hour, and 4wt% maleic anhydride aqueous solution and 1wt% ammonium persulfate aqueous solution were added, the mass ratio of chlorinated polyvinyl chloride, acetone, 4wt% maleic anhydride aqueous solution and 1wt% ammonium persulfate aqueous solution was 20:180:50:45, and the mixture was reacted at 80°C for 2 hours. After the reaction was completed, the filter cake was filtered and washed with 70°C hot water 5 times the mass of the filter cake, and dried at 70°C for 8 hours to obtain maleic anhydride grafted chlorinated polyvinyl chloride.
[0113] Comparative Example 3
[0114] This comparative example discloses a method for preparing a polyvinyl chloride material, comprising the following steps:
[0115] Step (1), mixing maleimide monomer, styrene, methyl acrylate, modified hydrotalcite, and dimethyl sulfoxide, adding azobisisobutyronitrile, the mass ratio of maleimide monomer, styrene, methyl acrylate, modified hydrotalcite, dimethyl sulfoxide, and azobisisobutyronitrile is 9:13:5:10:350:0.3, reacting at 70°C for 24h, after the reaction is completed, filtering, taking the filter cake, adding 5 times the mass of the filter cake for washing, and drying at 50°C for 16h to obtain a thermal stabilizer;
[0116] Wherein, the maleimide monomer is prepared by the following steps:
[0117] Mix and dissolve N-(4-hydroxyphenyl)maleimide, paraformaldehyde, and 1,4-dioxane, add p-methylaniline, the mass ratio of N-(4-hydroxyphenyl)maleimide, p-methylaniline, paraformaldehyde, and 1,4-dioxane is 7.2:4.1:2.2:20, react at 85°C for 10 hours, and after the reaction, remove the solvent 1,4-dioxane by rotary evaporation at 80°C to obtain a reaction product, add ether 5 times the mass of the reaction product to precipitate, let stand for 0.5 hours, filter, take the filter cake, and dry it at 50°C for 16 hours to obtain a maleimide monomer;
[0118] Wherein, the modified hydrotalcite is prepared by the following steps:
[0119] The hydrotalcite and water were stirred and mixed at a temperature of 40° C., 12 wt % sodium dodecyl sulfate aqueous solution and 3.5 wt % acrylic acid aqueous solution were added, the mass ratio of hydrotalcite, water, 12 wt % sodium dodecyl sulfate aqueous solution and 3.5 wt % acrylic acid aqueous solution was 1:25:28:25, 0.1 mol / L dilute nitric acid was added to adjust the pH value to 4, the reaction was carried out at a temperature of 60° C. for 4 h, and after the reaction was completed, the mixture was cooled to room temperature, filtered, and the filter cake was taken, and water 5 times the mass of the filter cake was added to wash until it was neutral, and dried at a temperature of 50° C. for 20 h to obtain a modified hydrotalcite;
[0120] Step (2), mixing polyvinyl chloride, maleic anhydride grafted chlorinated polyvinyl chloride, and a heat stabilizer in a mass ratio of 109:20:8, melt-extruded at a temperature of 170° C. through a twin-screw extruder, cooled and pelletized to obtain a polyvinyl chloride material;
[0121] Wherein, maleic anhydride grafted chlorinated polyvinyl chloride comprises the following steps to prepare:
[0122] Chlorinated polyvinyl chloride and acetone were mixed and swelled at 80°C for 1 hour, and 4wt% maleic anhydride aqueous solution and 1wt% ammonium persulfate aqueous solution were added, the mass ratio of chlorinated polyvinyl chloride, acetone, 4wt% maleic anhydride aqueous solution and 1wt% ammonium persulfate aqueous solution was 20:180:50:45, and the mixture was reacted at 80°C for 2 hours. After the reaction was completed, the filter cake was filtered and washed with 70°C hot water 5 times the mass of the filter cake, and dried at 70°C for 8 hours to obtain maleic anhydride grafted chlorinated polyvinyl chloride.
[0123] In the above embodiments and comparative examples: N-(4-hydroxyphenyl)maleimide is from Wuhan Kanos Technology Co., Ltd., CAS No.: 7300-91-6; paraformaldehyde is from Shanghai Aladdin Biochemical Technology Co., Ltd., item No. C104190, CAS No.: 30525-89-4; p-methylaniline is from Hubei Xinghengye Technology Co., Ltd., CAS No.: 106-49-0; hydrotalcite is from Hubei Xinyuhong Biomedical Technology Co., Ltd., product name magnesium aluminum hydrotalcite, average particle size 100nm, magnesium aluminum molar ratio of 2.25, CAS No.: 11097-59-9; polyvinyl chloride From Japan Taiyang Company, model TH-1000; styrene-acrylonitrile copolymer is from Shanghai McLean Biochemical Technology Co., Ltd., item number P909297, acrylonitrile content 25wt%; benzophenone-4,4'-dicarboxylic acid is from Shanghai Aladdin Biochemical Technology Co., Ltd., item number B153134, CAS number: 964-68-1; montmorillonite is from Zhejiang Huate New Materials Co., Ltd., product name sodium montmorillonite, its cation exchange capacity is 90mequiv / 100g, particle size 200 mesh; chlorinated polyvinyl chloride is from Weifang Hanghao New Material Technology Co., Ltd., model CPVC J-700, chlorine content 66%.
[0124] Test example
[0125] The comprehensive performance tests were conducted on the polyvinyl chloride materials prepared in Examples 1-5 and Comparative Examples 1-3. The specific test results are shown in Tables 1 and 2:
[0126] Table 1
[0127]
[0128]
[0129] Table 2
[0130]
[0131] The detection of various indicators in Table 1 and Table 2 is based on the following standards: tensile strength is measured with reference to GB / T1040-1992 "Test Method for Tensile Properties of Plastics"; Vicat softening temperature is measured with reference to GB / T8802-2001 "Determination of Vicat Softening Temperature of Thermoplastic Plastic Pipes and Fittings"; UV aging resistance is represented by light aging weight loss rate, which is measured with reference to GB / T16422.3-2014 "Plastic Laboratory Light Source Exposure Test Method Part 3: Fluorescent UV Lamp", and the test time is 10 days; corrosion resistance test includes: the polyvinyl chloride materials prepared in Examples 1-5 and Comparative Examples 1-3 are prepared into test specimens with reference to GB / T1040-1992 "Test Method for Tensile Properties of Plastics", recorded as samples 1-8, and samples 1-8 are respectively immersed in 1 mol / L sodium hydroxide aqueous solution and 1 mol / L hydrogen chloride aqueous solution for 12 hours, and the acid immersion weight loss rate and alkali immersion weight loss rate of the samples are recorded respectively.
[0132] It can be seen from the test results in Table 1 and Table 2 that the polyvinyl chloride material prepared by the present invention has excellent heat resistance, corrosion resistance and light aging resistance, and good mechanical properties.
[0133] The hydrotalcite absorbs the hydrogen chloride released by the thermal degradation of polyvinyl chloride, reduces the concentration of free hydrogen chloride in the matrix, effectively inhibits the self-catalytic degradation reaction of polyvinyl chloride by hydrogen chloride, and improves the thermal stability of polyvinyl chloride; the maleimide monomer with good heat resistance is used as a polymerization monomer, and the carbon-carbon double bond is used to react and copolymerize with the modified hydrotalcite, styrene, and methyl acrylate to generate a block copolymer with good compatibility with polyvinyl chloride, thereby improving the compatibility of the modified hydrotalcite with the polyvinyl chloride matrix, and the prepared heat stabilizer can effectively improve the thermal stability of polyvinyl chloride;
[0134] In Comparative Example 1, the hydrotalcite has no surface modification, and its compatibility with the polyvinyl chloride matrix is reduced. The hydrotalcite is easily agglomerated, which affects the comprehensive performance of the material. Therefore, the mechanical properties, heat resistance, light aging resistance, and corrosion resistance of Comparative Example 1 are all reduced. In Comparative Example 2, no maleimide monomer is added to the heat stabilizer, and the maleimide structure and oxazine ring structure with good heat resistance are lacking. Therefore, the heat resistance of Comparative Example 2 is lower than that of the embodiment.
[0135] There is a good interaction force between the acrylonitrile structure in the styrene-acrylonitrile copolymer and the polar groups such as the chlorine atoms of polyvinyl chloride, which can promote the plasticization of polyvinyl chloride during processing and melting. In addition, since the styrene-acrylonitrile copolymer and the substituted acrylonitrile ultraviolet absorber have a partially similar structure and have a strong absorption capacity for ultraviolet light, the rate of dehydrochlorination of polyvinyl chloride can be inhibited, and the plasticizer with ultraviolet absorption can be used to improve the light stability of polyvinyl chloride. The hydrotalcite in the heat stabilizer and the montmorillonite in the plasticizer both have a layered structure, which can extend the path of corrosion penetration when dispersed in the polyvinyl chloride matrix, further improving the corrosion resistance of the material.
[0136] Comparative Example 3 does not add styrene-acrylonitrile copolymer and plasticizer, lacks the improvement effect of styrene-acrylonitrile copolymer with ultraviolet absorption function and copolyester in the plasticizer on the light aging performance of the material. At the same time, since both styrene-acrylonitrile copolymer and plasticizer have plasticizing effect on polyvinyl chloride, the flexibility of the material can be improved. Therefore, the ultraviolet aging resistance of Comparative Example 3 is lower than that of the embodiment, but the tensile strength is higher than that of the embodiment. Since montmorillonite in the plasticizer can improve the corrosion resistance of the material, the corrosion resistance of Comparative Example 3 is lower than that of the embodiment.
[0137] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a high temperature resistant and corrosion resistant polyvinyl chloride material, characterized in that: The following steps are involved: Step (1), mixing maleimide monomer, styrene, methyl acrylate, modified hydrotalcite and dimethyl sulfoxide, adding azobisisobutyronitrile, reacting, filtering, washing and drying after the reaction is completed to obtain a thermal stabilizer; Wherein, the maleimide monomer is prepared by the following steps: N-(4-hydroxyphenyl)maleimide, paraformaldehyde and 1,4-dioxane are mixed and dissolved, p-methylaniline is added, and the reaction is carried out. After the reaction is completed, the solvent 1,4-dioxane is removed by rotary evaporation, a precipitant is added for precipitation, the mixture is allowed to stand, filtered and dried to obtain a maleimide monomer; Step (2), polyvinyl chloride, maleic anhydride grafted chlorinated polyvinyl chloride, styrene-acrylonitrile copolymer, heat stabilizer and plasticizer are uniformly mixed, melt-extruded, cooled and pelletized to obtain a high temperature resistant and corrosion resistant polyvinyl chloride material.
2. The method for preparing a high temperature resistant and corrosion resistant polyvinyl chloride material according to claim 1, characterized in that: In the step (1), the mass ratio of maleimide monomer, styrene, methyl acrylate, modified hydrotalcite, dimethyl sulfoxide and azobisisobutyronitrile is 9-10:13-15:5-6:10:350-400:0.3-0.4; and the reaction conditions are: reacting at a temperature of 70-80° C. for 20-24 hours.
3. The method for preparing a high temperature resistant and corrosion resistant polyvinyl chloride material according to claim 1, characterized in that: The modified hydrotalcite in step (1) is prepared by the following steps: The hydrotalcite is mixed with water by stirring, and a sodium dodecyl sulfate aqueous solution and acrylic acid are added as a regulator to adjust the pH value, and the reaction is carried out. After the reaction is completed, the mixture is cooled, filtered, washed, and dried to obtain a modified hydrotalcite; The mass ratio of hydrotalcite, water, sodium dodecyl sulfonate aqueous solution and acrylic acid aqueous solution is 1:25-30:28-30:25-28, the sodium dodecyl sulfonate aqueous solution is 12wt% sodium dodecyl sulfonate aqueous solution, and the acrylic acid aqueous solution is 3.5wt% acrylic acid aqueous solution; the reaction conditions are: reacting at a pH value of 4-5 and a temperature of 60-70°C for 3-4h.
4. The method for preparing a high temperature resistant and corrosion resistant polyvinyl chloride material according to claim 1, characterized in that: In the step (1) of preparing the maleimide monomer, the mass ratio of N-(4-hydroxyphenyl)maleimide, p-methylaniline, paraformaldehyde and 1,4-dioxane is 7.2-7.5:4.1-4.5:2.2-2.5:20-30; and the reaction conditions are: reacting at a temperature of 85-95° C. for 8-10 hours.
5. The method for preparing a high temperature resistant and corrosion resistant polyvinyl chloride material according to claim 1, characterized in that: In the step (2), the mass ratio of polyvinyl chloride, maleic anhydride grafted chlorinated polyvinyl chloride, styrene-acrylonitrile copolymer, heat stabilizer and plasticizer is 100:20-25:4-6:8-10:5-6; the melt extrusion conditions are: melt extrusion at a temperature of 170-180° C. through a twin-screw extruder.
6. The method for preparing a high temperature resistant and corrosion resistant polyvinyl chloride material according to claim 1, characterized in that: The plasticizer in step (2) is prepared by the following steps: Mix benzophenone-4,4'-dicarboxylic acid, 1,10-decanediol and adipic acid, add stannous octoate and react. After the reaction is completed, heat up and continue the reaction. After the reaction is completed, copolyester is obtained. Mix the copolyester with montmorillonite, melt blend, extrude and granulate to obtain a plasticizer.
7. The method for preparing a high temperature resistant and corrosion resistant polyvinyl chloride material according to claim 6, characterized in that: In the preparation of the plasticizer, the molar ratio of benzophenone-4,4'-dicarboxylic acid, 1,10-decanediol and adipic acid is 0.8-1:5:4-4.2; the amount of stannous octoate added is 3% of the mass of 1,10-decanediol; the reaction conditions are: reacting for 5-6 hours at a temperature of 170-180°C in a nitrogen atmosphere; the continued reaction conditions are: continuing the reaction for 1.5-2 hours at a vacuum degree of 200-250Pa and a temperature of 200-220°C; the mass ratio of copolyester to montmorillonite is 100:20-30; and the melt blending conditions are: melt blending at a temperature of 110-120°C through a twin-screw extruder.
8. The method for preparing a high temperature resistant and corrosion resistant polyvinyl chloride material according to claim 1, characterized in that: The maleic anhydride grafted chlorinated polyvinyl chloride in step (2) is prepared by the following steps: The chlorinated polyvinyl chloride is mixed with acetone to swell, and a maleic anhydride aqueous solution and an ammonium persulfate aqueous solution are added to react. After the reaction is completed, the mixture is filtered, washed, and dried to obtain maleic anhydride grafted chlorinated polyvinyl chloride; The mass ratio of chlorinated polyvinyl chloride, acetone, maleic anhydride aqueous solution and ammonium persulfate aqueous solution is 20:180-220:50-55:45-50, the maleic anhydride aqueous solution is 4wt% maleic anhydride aqueous solution, and the ammonium persulfate aqueous solution is 1wt% ammonium persulfate aqueous solution; the reaction conditions are: reacting at a temperature of 80-90°C for 1.5-2h.
9. A high temperature resistant and corrosion resistant polyvinyl chloride material prepared based on the preparation method of the high temperature resistant and corrosion resistant polyvinyl chloride material as claimed in any one of claims 1 to 8.
10. A high temperature resistant and corrosion resistant polyvinyl chloride pipe prepared based on the high temperature resistant and corrosion resistant polyvinyl chloride material as claimed in any one of claims 1 to 8.
Citation Information
Patent Citations
Heat-resistant wear-resistant PVC pipe
CN101696306A
